Bill 103 : Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec - Bourhis, Richard Y.; Foucher, Pierre (Quebec Community Groups Network (QCGN), 2010)
The first part of this brief deals with the declining vitality of the English speaking communities of Quebec (ESCQ) and the strength of the dominant Québécois francophone majority in the Province. We argue that a key premise of Bill 103 is based on the erroneous notion that the French language and its speakers are threatened in the Province of Quebec. This false premise brings the current government to draft Bill 103 with regulations making it virtually impossible for Allophone and immigrant children to be approved as pupils in the publicly funded English schools of the Province. As the past Education Minister Michele Courchesne stated on June 3rd 2010 “I won’t deny that the objective (of Bill 103) is to have as few as possible (approved)”.

Collective Rights and the Declining Vitality of the English-speaking communities of Quebec - Leith, Linda; Macleod, Roderick (2010)

Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec : Brief to the Committee on Culture and Education with Regards to the General Consultation and Public Hearings on Bill 103, An Act to Amend the Charter of the French Language and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2010)
Our brief deals with the declining vitality of the English-speaking communities of Quebec (ESCQ) and the relative strength of the Francophone majority. The QCGN‟s goal is to demonstrate that our minority communities are not a threat to the majority, but a constituency that strengthens Quebec society. We expose the detrimental effect that Quebec's habit of emphasising an exclusionary notion of its society has on its minority population. Finally, we seek to attain official recognition of the historic and ongoing contributions our minority makes to Quebec society and achieve legal protection of minority rights and freedoms.
Keywords: Official Language Minority Community (OLMC)

Les droits collectifs et la vitalité en déclin des communautés québécoises d’expression anglaise : Mémoire présenté à la Commission de la culture et de l’éducation dans le cadre de la consultation générale et des audiences publiques sur le projet de loi numéro 103, loi modifiant la Charte de la langue française et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2010)
Our brief deals with the declining vitality of the English-speaking communities of Quebec (ESCQ) and the relative strength of the Francophone majority. The QCGN‟s goal is to demonstrate that our minority communities are not a threat to the majority, but a constituency that strengthens Quebec society. We expose the detrimental effect that Quebec's habit of emphasising an exclusionary notion of its society has on its minority population. Finally, we seek to attain official recognition of the historic and ongoing contributions our minority makes to Quebec society and achieve legal protection of minority rights and freedoms.
Keywords: Official Language Minority Community (OLMC)

Presentation to the Standing Committee on Official Languages on Immigration as a Development Tool in Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2010)